Pengaruh Sikap Guru pada Keberhasilan Belajar Siswa di Sekolah Dasar 55/Sridadi - Rahmanda, Febby; Tanti, Riska; Voseka, Revina; Rizkia, Syarifah; Putri, Adella Rahmadi; Hayu, Intan Dwi (MASALIQ, 2023)
Education has an important role in improving quality human resources with intelligence and skills. Education must be carried out consciously and the learning process is planned so that everything that is done by teachers and students is a learning process to achieve an educational goal. This study aims to determine the effect of teacher attitudes on student learning success. In research using quantitative methods with survey analysis. The results that can be obtained from this study are that there is a positive and significant influence between teacher attitudes on student learning success at SDN 55/1 Sridadi as evidenced by the results of a simple regression analysis conducted